PERSEPSI KEMUDAHAN, DAYA TARIK PROMOSI DAN PERSEPSI KEMANFAATAN PENGARUHNYA PADA MINAT MASYARAKAT MENGGUNAKAN APLIKASI E-WALLET - Dihin Septyanto; Nanda Andari Praudy (Jurnal Keislaman, 2022)
This study aims to determine the effect of public perceptions of e-wallets or electronic wallets on Interests in Using the LinkAja e-wallet application in Tangerang Regency. Sampling was carried out using a non-probability sampling method using a purposive sampling technique of 130 respondents with an age limit of 17 years and a minimum of having used the LinkAja e-wallet application. The number of statements submitted to respondents was 26 statement items, consisting of 6 items of Perceived Convenience statement, 6 items of Promotional Attractiveness statements, 6 items of Perceived Usefulness Statement, and 8 items of Interest in Using. The data analysis technique used in this research is validity test, reliability test, descriptive analysis, multiple linear regression, classical assumption test, F test, t test, and coefficient of determination test (R2). The analytical method used is multiple linear analysis to determine the direct and indirect effects between variables. The results of this study indicate that Perceived Convenience, Promotional Attractiveness, and Perceived Usefulness simultaneously influence Intention to Use. Partially, the variable Perceived Ease of Use has a significant and positive effect on Interest in Using. Perceived usefulness has a significant and positive effect on Intention to Use, while the Attractiveness of Promotion has no significant effect on intention to use, this shows that apart from the fact that the existing promotions are less attractive, users do not see promotions as an aspect that influences decision making in using the LinkAja e-wallet. Respondents see more about the extent to which the e-wallet provides ease of use and benefits.